Introducing the Study of Life and Death Education to Support the Importance of Positive Psychology: An Integrated Model of Philosophical Beliefs, Religious Faith, and Spirituality - Phan, Huy P.; Ngu, Bing H.; Chen, Si Chi; Wu, Lijuing; Lin, Wei-Wen; Hsu, Chao-Sheng (Frontiers in Psychology, 2020)
Life education, also known as life and death education, is an important subject in Taiwan with institutions offering degree programs and courses that focus on quality learning and implementation of life education. What is interesting from the perspective of Taiwanese Education is that the teaching of life education also incorporates a number of Eastern-derived and conceptualized tenets, for example, Buddhist teaching and the importance of spiritual wisdom. This premise contends then that life education in Taiwan, in general, is concerned with the promotion, fulfillment, and cherishing of quality life experiences (e.g., personal contentment, happiness). One example of life education, which resonates with other spiritual beliefs and religious faiths (e.g., Hinduism), is related to spiritual cultivation and the enlightenment of life wisdom. Our own teaching of the subject, likewise, places emphasis on the goal of teaching students to seek meaningful understanding of and appreciation for three major, interrelated components of life education: life wisdom, life practice, and life care. Life education is a beneficial subject as its theoretical understanding may help individuals cope with pathologies and negative life experiences. One negative life experience, in this case, is the ultimate fate of humankind: death. Approaching death and/or the onset of grief is something that we all have to experience. How does one approach death? It is not easy feat and, of course, grief for a loved one is personal and some of us struggle with this. We contend that spiritual cultivation and enlightenment, arising from life education, may assist us with the coping of death (e.g., the possibility of transcendence beyond the realm of life). Forming the premise of the present article, we propose that a person’s ‘spiritual and enlightened self’, reflecting the convergence of three major aspects of life education (i.e., Philosophical reflection, Enrichment of personal well-being, and Spiritual cultivation), would result in the initiation and creation of a number of virtues and positive characteristics – for example: having a positive outlook in life, showing compassion, forgiveness, etc. These virtues and quality characteristics, from our philosophical reasoning, are equivalent to those qualities that positive psychology advocates for.